Peningkatan Capacity Building Aparatur Nagari Suayan dalam Pemanfaatan Kios SKM dan Menganalisis Data Survey Kepuasan Masyarakat - Dasman Lanin; Boni Saputra; Lince Magriasti; Afifah Asriati; Dwi Finna Syolendra; Muhammad Nasrullah (Universitas Lancang Kuning, 2023)
This community service activity is an advanced stage for the second year, funded by the Institute for Research and Community Service (LPPM) Universitas Negeri Padang. This activity aims to assist in increasing the knowledge and skills of Nagari Suayan officials in conducting technology-based community satisfaction surveys (SKM) in the form of utilizing SKM kiosk machines and activities to analyze SKM results data. The SKM Kiosk is an SKM survey recording machine that utilizes digital technology. The method in this activity uses training and mentoring,